Interpretation of Thyroid Blood Tests Using Mamdani Type Fuzzy Logic Sets - (:unkn) unknown (IEEE, 2013)
Nowadays, the number of diseases related to the thyroid gland function inefficiency is an increasing problem all around the world. Studies shows that in Turkey the ratio of incidence of this kind of diseases is between 10% - 20%. But in our country the time for consultation is very limited. Therefore blood test results and other evidences which point out the disease can be ignored. The purpose of this study is to give advices to the thyroid inefficiency patients according to their blood test results. To achieve this goal we used Mamdani Type Fuzzy Logic system which is tested according to the possible blood test results of thyroid inefficiency patients.